Pemetaan Implementasi Pendidikan Karakter di Sekolah Dasar se-Kota Kupang - Yulsy Marselina Nitte; Vera Rosalina Bulu (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This research aimed to describe the implementation of character education in schools, in terms of planning, implementation and evaluation of the character education. This research method used survey, it was conducted in Elementary Schools of Kupang City. Samples were selected using random sampling cluster area technique so that from a population of 134 schools selected 21 schools representing 6 existing sub-districts. The instruments used are questionnaire and interview guidelines. This research uses qualitative descriptive analysis techniques. This study resulted in; (1) The planning aspect of character education began in 2011/2012 academic year. The initiator was the education office of Kupang City in collaboration with schools’ internal parties. The reason of implementing this character education were to change students’ behaviours into noble people in balance with graduates expected competencies, to help students make wise decisions, and be able to distinguish between good and bad, and to cultivate leadership and responsible characters either in family, school or society. (2) Implementation aspect involved actors of implementation and target of character education including principal, teachers, officers and students. The integration of character education in schools was done through subjects’ learning, habituation and extracurricular activities. (3) The evaluation phase covered impact of implementation, barriers to implementation and solutions to overcome those obstacles.